ХАЛҚ ТАЪЛИМИ ХОДИМЛАРИ МАЛАКАСИНИ ОШИРИШ ТИЗИМИНИ КЎП ВЕКТОРЛИ ЁНДАШУВ АСОСИДА ТАКОМИЛЛАШТИРИШНИНГ ЎЗИГА ХОС ХУСУСИЯТЛАРИ - Ибрагимов, А.А. (SCIENCE and SOCIETY, 2017)
The article is devoted to the multi-vector approach in the development of the system of improving qualification of public education’ personnel. On the basis of scientific research analysis there were defined the directions and conditions of the multi-vector approach.
Keywords: vector; educational vector; multi-vector; module-accumulated professional development; scientific and methodological accompaniment; trajectory of individual education